2016
DOI: 10.1111/jnc.13630
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic glycolysis during brain activation: adrenergic regulation and influence of norepinephrine on astrocytic metabolism

Abstract: Aerobic glycolysis occurs during brain activation and is characterized by preferential up-regulation of glucose utilization compared with oxygen consumption even though oxygen level and delivery are adequate. Aerobic glycolysis is a widespread phenomenon that underlies energetics of diverse brain activities, such as alerting, sensory processing, cognition, memory, and pathophysiological conditions, but specific cellular functions fulfilled by aerobic glycolysis are poorly understood. Evaluation of evidence der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(184 citation statements)
references
References 324 publications
(392 reference statements)
1
164
0
1
Order By: Relevance
“…Additionally, genetic manipulation studies suggested a physiological role of metabolic neuron-glia coupling in intact mice and drosophila [29–31]. However, the physiological role of the ANLS in brain energetics is still under scrutiny [32]. Future studies are warranted to evaluate actual lactate transport rates in vivo .…”
Section: Energy Metabolism In the Brainmentioning
confidence: 99%
“…Additionally, genetic manipulation studies suggested a physiological role of metabolic neuron-glia coupling in intact mice and drosophila [29–31]. However, the physiological role of the ANLS in brain energetics is still under scrutiny [32]. Future studies are warranted to evaluate actual lactate transport rates in vivo .…”
Section: Energy Metabolism In the Brainmentioning
confidence: 99%
“…The brain’s utilization of glucose exceeds that predicted from the rate of oxygen consumption (Boyle et al, 1994; Dienel and Cruz, 2016; Madsen et al, 1995; Vaishnavi et al, 2010). Such mitochondrial-independent glucose consumption varies regionally, developmentally, and according to neuronal activity (Goyal et al, 2014; Madsen et al, 1995; Settergren et al, 1976; Vaishnavi et al, 2010), and reflects ‘aerobic glycolysis’ and pentose phosphate pathway (PPP) activities.…”
Section: Introductionmentioning
confidence: 89%
“…20 It is not clear how suppression of neuronal activity over and above that from anesthesia would influence recovery from brain injury, but signaling and metabolic properties of lactate flooding must be taken into account with evaluating outcome.…”
Section: Potential Consequences Of Lactate Floodingmentioning
confidence: 99%
“…For example, glutamate-evoked lactate release is not a robust phenotype of cultured astrocytes, glutamate is oxidized by cultured astrocytes to generate more ATP than glycolysis, lactate oxidation coupled with glycolysis requires a parallel rise in CMR O2 with CMR glc during brain activation that does not occur (i.e., OGI falls during brain activation), and lactate oxidation would cause trapping of labeled metabolites of glucose to the same extent as the rise in glycolytic rate, which does not occur during brain activation. 20 For these reasons, lactate shuttling and utilization have been a controversial issue. [45][46][47][48][49][50][51][52][53][54] Importantly, in vitro studies have shown that lactate can maintain ATP levels but not sustain neuronal signaling, underscoring unidentified but critical roles of glucose metabolism upstream of pyruvate/lactate for neuronal function.…”
Section: Why Flood the Brain With Lactate?mentioning
confidence: 99%
See 1 more Smart Citation